Pedagogical Foundations of Designing Integrated Learning Modules - Qahhorova Maftuna Baxtiyor qizi (Researchparks Publishing, 2026)
This article examines the theoretical and practical pedagogical foundations of designing integrated learning modules. It reviews the historical development of modular education, scientific approaches, integration principles, and the didactic underpinnings of modular curriculum design. Special attention is devoted to systems thinking, competency-based education, and the methodology of defining learning outcomes in module design. The findings demonstrate that appropriately designed integrated modules increase students' knowledge quality by 34% and practical skills by 47%. The article serves as a practical guide for university faculty, educational administrators, and curriculum developers.